Tratamento de resíduos sólidos em reator anaeróbio de duplo estágio visando a obtenção de bioenergia e créditos de carbono: estudo de caso CEASAMINAS - Eduardo da Silva Guimaraes Martins da Costa (2011)
The use of biodegradable organic solid waste as biomass in order to generate energy is a good practice, and can help increase the availability of energy for mankind. Such wastes have a high potential for biogas generation with low carbon emissions to the atmosphere, and may constitute an interesting alternative energy source. In order to find out the energy potential of biodegradable organic solid waste produced at CEASAMINAS in its warehouse in Contagem-MG, in this study was evaluated the efficiency and applicability of a two-stage anaerobic treatment of these wastes with the production of biogas and carbon credits. To carry out the work, a complex and automated experimental apparatus was built, using a two-stage anaerobic digestion system. The digestion system used is innovative and has the advantage of producing high quality biogas (> 70% CH4) that allow the control of the biogas production by varying the application rate of COD in the methanogenic reactor over time. Another objective of the research was to evaluate the use of biogas to produce electricity and heat through a CHP engine (Combined Heat Power), and possible carbon credits to be obtained with the process. To simulate the waste produced by CEASAMINAS in 2009, 4 tests were performed every 14 days. The results showed that the apparatus worked well, enabling the prediction of the production of biogas with CEASAMINAS´ waste. The experiments showed that it is possible to produce 130,41 LBiogas.kgSV-1, with an average CH4 percentage of 73.13%. Under these conditions, in average, it is also possible to produce 536.786 kWh of electricity and 1.090.299 kWh of thermal energy with CEASAMINAS wastes. With such energy availability, the use of a CHP engine with 61,27 kW power working 24 h.day-1 is possible, with the recovery of the equivalent power of 124,46 kW in heat. Besides generating energy, the achievement of a 13.791,51 tCO2e in carbon emission reductions in 21 years is possible, enabling such reduction to become carbon credits through CDM projects.